BERFIKIR STATEGIS UNTUK MENCAPAI TUJUAN ORGANISASI DALAM IKLIM GELOMBANG KEKACAUAN (CHAOS) - Arif Arif (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
Strategic thinking becomes the key of success for achieving organization goal. Strategy corresponds to how things are executed based upon set-up plans to gain maximum result. Therefore, organization is obliged to have its own strategy. Four basic principles have emerged in correspondence to new strategy: They have functional roles in human life cycle.